2012
DOI: 10.1186/1471-2474-13-40
|View full text |Cite
|
Sign up to set email alerts
|

Normative values for the bath ankylosing spondylitis functional index in the general population compared with ankylosing spondylitis patients in Morocco

Abstract: BackgroundThe Bath Ankylosing Spondylitis Functional Index (BASFI) has been commonly used in rheumatology to quantify functional disability in patients with Ankylosing Spondylitis (AS). Our aim was to evaluate the discriminating power of BASFI and determine the best cutoff score of this index in the general population compared with AS patients.MethodsA cross-sectional study that included 200 patients suffering from AS and 223 subjects from the general population matched for age and sex was carried-out. The dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
(12 reference statements)
1
7
0
Order By: Relevance
“…The observed differences in age, disease duration, employment and spinal mobility between patients with and without SGE were in line with indications from previous studies [12,13,18]. However, both the lower medication use in patients with SGE and the comparable health status between patients with and without SGE were surprising, as health status and physical functioning may deteriorate with age in axSpA patients, similar to spinal mobility [18][19][20]. It can be speculated that SGE participation prevented deterioration of health status and the need for analgesics, since previous studies have shown positive effects of SGE on symptoms, fitness and functioning [7,8,10,11].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The observed differences in age, disease duration, employment and spinal mobility between patients with and without SGE were in line with indications from previous studies [12,13,18]. However, both the lower medication use in patients with SGE and the comparable health status between patients with and without SGE were surprising, as health status and physical functioning may deteriorate with age in axSpA patients, similar to spinal mobility [18][19][20]. It can be speculated that SGE participation prevented deterioration of health status and the need for analgesics, since previous studies have shown positive effects of SGE on symptoms, fitness and functioning [7,8,10,11].…”
Section: Discussionsupporting
confidence: 88%
“…Findings from previous studies suggest that only a small minority of axSpA patients engages in axSpA-specific SGE [12,16,17] and that this concerns relatively old axSpA patients [12,13]. This should be taken into account when providing personal exercise advice, as older axSpA patients, on average, have worse spinal mobility [18], slightly worse health status [19,20] and a higher risk of comorbidities [21].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we evaluated the associations with disease activity and functional indices. For this purpose, the variables of interest were categorized as follows: low (< 0.5 mg/dl) or high (≥ 0.5 mg/dl) CRP; inactive disease (≤ 1.3) or low/high/very high ASDAS (> 1.3), BASDAI ≤ 4 or > 4; BASFI ≤ 1.5 or > 1.5 [ 13 ]; BASMI 0 or > 0.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary outcomes were (a) persistence of active disease (BASDI ≥ 4) and (ASDAS-CRP > 1.3) in adulthood; (b) fulfillment of adult SpA criteria (both ASAS axial spA [7,17] and modified New York criteria [18]); and (c) predictors and associations of poor outcomes in adulthood. Poor outcome was defined as presence of BASDAI ≥ 4 [19], or ASDAS-CRP ≥ 2.1 [7] or BASFI ≥ 0.9 [17] or HAQ-DI ≥ 0.5 [8] for disease activity, functionality, or disability, respectively. Statistical analysis Descriptive data were presented as the median and interquartile range (IQR).…”
Section: Clinical Detailsmentioning
confidence: 99%